Cleopatra - Roller, Duane W. (Oxford Univ. Press, 2010)
Cleopatra's ancestry and background – The Ptolemaic heritage and the entanglement with Rome – Cleopatra's youth and education – Becoming queen (51-47 BC) – Consolidating the empire (47-40 BC) – The peak years (40-34 BC) – The operation of the kingdom – Royal administration – The royal building program – Isis and Dionysos – Foreign policy and the matter of Herod the Great – Scholarship and culture at the court of Cleopatra – Downfall (34-30 BC) – Outline of Cleopatra's life and career – Cleopatra's mother – Was Cleopatra a Roman citizen? – Some ancient literary descriptions of Cleopatra – Genealogy – The iconography of Cleopatra
9780195365535
Keywords: Biografie; Cleopatra; Cleopatra d. 30 B.C; Queens